2023
DOI: 10.1002/adma.202209941
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Oxygen Atoms Taking Tetrahedral Interstitial Sites in Medium‐Entropy Body‐Centered‐Cubic Solutions

Abstract: Interstitial solutes, such as carbon in steels, are effective solid‐solution hardening agents. These alloying elements are believed to occupy the octahedral interstices in body‐centered‐cubic (bcc) metals. Using deep‐sub‐angstrom‐resolution electron ptychography, here the first experimental evidence to directly observe individual oxygen atoms in a highly concentrated bcc solid solution—the (TiNbZr)86O12C1N1 medium‐entropy alloy (MEA)—is provided, whereby the interstitial sites in which the oxygen atoms are loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…[ 106 ] Alternatively, the contrast contributions from the top and bottom sections (the two exposed cross‐sectional surfaces that might be damaged by the ion beam) can be entirely excluded through computational imaging methods. [ 107 ]…”
Section: Real‐space Imaging Of 2d Tmds At the Atomic‐scalementioning
confidence: 99%
See 1 more Smart Citation
“…[ 106 ] Alternatively, the contrast contributions from the top and bottom sections (the two exposed cross‐sectional surfaces that might be damaged by the ion beam) can be entirely excluded through computational imaging methods. [ 107 ]…”
Section: Real‐space Imaging Of 2d Tmds At the Atomic‐scalementioning
confidence: 99%
“…[106] Alternatively, the contrast contributions from the top and bottom sections (the two exposed crosssectional surfaces that might be damaged by the ion beam) can be entirely excluded through computational imaging methods. [107] One notable example utilizing cross-sectional STEM imaging is the identification of Janus MoSSe, a unique type of TMDs with a broken out-of-plane symmetry and vertical dipole (Figure 4a). [108] The design of this Janus TMDs starts from removing the upper layer of S atoms in CVD-grown monolayer MoS 2 via hydrogen plasma treatment, and then replacing the upper layer H atoms with Se atoms.…”
Section: Cross-sectional Atomic-scale Investigationmentioning
confidence: 99%
“…In recent years, outside of the field of battery materials research, it has been reported that over-stoichiometric cations may locate at interstitial sites in various types of fcc lattices, [37][38][39][40][41][42] hinting at the possibility of over-stoichiometric chemical spaces for rock salt structures. Moreover, a number of pioneering works have indicated that interstitial sites (e.g., tetrahedral sites) in the fcc-or near-fcc-type cathodes may be occupied by cations, which also suggests that rock salt structures may host extra cations.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30][31] The presence of residual strain, arising from modulus mismatch and atomic size differences, comprises both volumetric and shear components, resulting in significant spreading. [32][33][34] The inherent lattice distortion in MPEAs allows for the accommodation of more interstitial atoms, [35,36] further intensifying the lattice distortion. By capitalizing on the synergistic effects of inherent substitutional solid solution strengthening and extreme interstitial solid solution strengthening, the material strength may be optimized.…”
Section: Introductionmentioning
confidence: 99%